Deceleration and acceleration capacities of heart rate in patients with hypertrophic cardiomyopathy: results of a five-year prospective study - D. A. Tsaregorodtsev; I. R. Bukia; M. A. Khalikova; E. A. Okisheva (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To study the features of deceleration capacity (DC) and acceleration capacity (AC) in patients with hypertrophic cardiomyopathy (HCM) and assess the correlation of these indicators with known complications and risk factors for sudden cardiac death (SCD).Material and methods. A total of 50 patients with HCM were examined. Comparable by sex and age, the control group included 50 individuals without cardiovascular diseases. All patients underwent 24-hour electrocardiographic monitoring with the determination of DC and AC. The follow-up period lasted 5 years. Lethal outcomes were recorded in 6%, including SCD — 4%.Results. Patients with HCM were characterized by significantly lower mean DC — 5,5 [3,7; 7,4] vs 7,8 [7,1; 8,5] ms (p=0,0001) and significantly higher AC– -7,4 [-8,9; -5,8] vs -9,3 [-10,0; -8,6] ms (p=0,001) compared with the control group. In 36% of patients with HCM, pathological values of DC ≤4,5 ms were detected, while in all individuals in the control group, DC corresponded to a favorable prognosis (p=0,001). In patients with and without nonsustained ventricular tachycardia (NSVT), a decrease in DC was detected in 56% and 25,5% (p=0,043), respectively, while with and without heart failure (HF) — in 78% and 27% (p=0,016), respectively. In patients with HF (p=0,003) and paroxysmal atrial fibrillation (p=0,023), mean DC values were significantly lower than in patients without these complications. HF was an independent predictor of DC reduction. DC decrease was not associated with an increase in SCD risk estimated using the HCM Risk-SCD calculator.Conclusion. Patients with HCM compared with healthy individuals are characterized by lower DC and higher AC values. Among patients with HCM, a decrease in DC is typical for patients with a more severe disease course (HF, AF, NSVT). However, the rationale for using this indicator in SCD risk stratification needs to be clarified.